Paternalistic leadership and teamwork on employee performance at Sharia hotels: The mediating role of work-family conflict - Suherman, Usep Deden (BISMA (Bisnis dan Manajemen), 2025)
This study aims to examine how paternalistic leadership and teamwork demands influence employee effectiveness, with work-family conflict serving as a mediating factor. In the hospitality industry, especially in Sharia hotels, employee performance is crucial for maintaining service quality and customer satisfaction. Leadership style and teamwork demands can significantly impact employee effectiveness, particularly when work-family conflict arises as a mediating factor. This research employed an explanatory survey involving 344 employees from Sharia hotels. Partial Least Square-Structural Model (PLS-SEM) analysis is implemented to analyse the data. The results show that paternalistic leadership and teamwork positively influence employees’ performance. Work-family conflict is positively influenced by paternalistic leadership and collaboration. Work-family conflict, which is brought on by paternalistic leadership and teamwork, influences employee performance. This study implies that Sharia hotel management should adopt paternalistic leadership and foster teamwork to enhance employee performance while being mindful of work-family conflict. Implementing supportive policies and promoting a balanced work environment can reduce conflict and improve overall effectiveness among staff.